NATIVIZATION AND USE OF BORROWING WORDS IN BAHASA INDONESIA - Husin, Saifuddin Ahmad (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Bahasa Indonesia, the national language of Indonesia, has traditionally borrowed items from the world’s classical languages, Sanskrit and Arabic. However, elements from European languages, especially English, have also massively influenced the expansion of Bahasa Indonesia’s lexicons. Massive influx of the latter has caused a controversy among Indonesia’s linguists and other experts. Should greater loan be made from the former, as traditional source of borrowings, or should Bahasa Indonesia borrow more from the latter, as the language of modernity symbol in Indonesia? The controversy has been cleverly resolved with the adaptation and combination of elements of seemingly conflicting sources to serve specifically Indonesian objectives. In the lexical modernization of Bahasa Indonesia, despite the apparent irreconcilability of the two approaches to the use of foreign borrowings, Indonesians are effectively utilizing in a systematic manner the diverse foreign languages that their rich and varied history has made available to them.Keywords: Lexical Borrowing, Nativization, Bahasa Indonesia, Language Modernization